CYBERSECURITY AND SOCIAL CONSCIOUSNESS: CONCEPTS OF IMMUNITY FORMATION - Evatov Burivoy Sobirjonovich (Sciental Journals Publishing, 2025)
This article explores the intersection of cybersecurity and social consciousness, proposing a conceptual framework for forming societal immunity against cyber threats. As digital environments become integral to modern life, cyber-attacks—ranging from data breaches to disinformation campaigns—threaten not only technological infrastructure but also social cohesion and trust. Drawing on interdisciplinary perspectives, this study examines how social consciousness, defined as collective awareness and adaptive behavior, can serve as a foundation for resilience against cyber threats. The article identifies key components of immunity formation: awareness, behavioral adaptation, and collaborative action. It integrates theoretical models, such as systems theory and social learning theory, with practical examples, including the 2020 SolarWinds attack and the 2021 Colonial Pipeline ransomware incident. Strategies for enhancing social immunity—public education, cross-sector collaboration, and technology-driven solutions like AI and blockchain—are critically analyzed. The findings suggest that fostering a proactive social consciousness is essential for sustainable cybersecurity, offering a novel contribution to the field by bridging technical and socio-psychological dimensions. Future research directions and policy implications are also discussed.
Keywords: Cybersecurity, social consciousness, cyber immunity, cyber threats, public awareness, behavioral adaptation, collaborative resilience, systems theory.